The Evaluation of Clinical and Genetic Characteristics of Primary Ciliary Dyskinesia - Melih Hangül; Abdullah Gurler (Galenos Publishing House, 2022)
Primary ciliary dyskinesia (PCD) is a clinically and genetically heterogeneous condition characterized by defective motile cilia activity. There is no "gold standard" diagnostic test currently available. In this article, we summarize the clinical and genotypic features of 25 children with PCD who received therapy at a single location in Turkey. This study was done between October 2020 and July 2022 as a retrospective cohort study in which the medical records of Turkish and refugee patients with PCD were reviewed regarding their medical history, clinical and radiologic findings, and genetic data. We evaluated the outcomes of 25 patients whose genetic results were reported to be associated with known PCD genes. The mean age of patients with PCD was 10.5 (±5). PICADAR scores ranged from 2 to 10, with the mean score being 6.1 (± 2.2). Age at diagnosis was shown to be moderately negatively correlated with PICADAR. (r;-0,502, p;0,01).16% DNAH5 within four patients, 16% with CCDC40 in four patients,12% with DNAAF2 in three patients, 8% with DNAH11 in two patients, 8% with TTC25 in two patients, 8% with DNAAF4 in two patients, 8% with CCNO in two patients 4% with DYNC2H1 in one patient, 4% with DNAI1 in one patient, 4% with ARMC4 in one patient,4% with RSPH4A in one patient, 4% with HYDIN in one patient,4% with CCDC65 in one individual from each PCD gene. The association between the phenotype and genotype of PCD patients in the southeast Anatolian region of our nation was explored for the first time in this study. Additionally, PCD patients with PIBO were reported for the first time with CCNO defects. Genotype and phenotype studies will help us determine the prognosis of patients in the future. These findings should increase our knowledge of PCD pathogenic pathways, hence enhancing early illness diagnosis, disease treatment, and prognosis.